Separation of Rhodamine B Dye from Aqueous Media Using Natural Pomegranate Peels - Zainab Mohammad Saigl; Arwa Mohammed Ahmed (Universitas Gadjah Mada, 2021)
Natural pomegranate peels (PPs) ground powder was proved as effective natural biomass for the separation of RhB from different aqueous media by batch adsorption experiments. Several parameters that affect the maximum adsorption capacity toward RhB dye, e.g., the pH solution, initial dye concentration, adsorbent dosage, shaking time, and solution temperature in the sorption behavior, were studied. Adsorption of RhB dye from aqueous media of pH ≈ 5 reached equilibrium in 10 min and was independent of the initial concentration of RhB. RhB dye sorption followed pseudo-second order kinetic with an overall rate constant (k2) of 0.04 g mg–1 min–1. Furthermore, the sorption isotherm was found 31.95 ± 0.02 mg g–1 for the sorption capacity of RhB onto PPs. The thermodynamic parameters (ΔH, ΔS, and ΔG) of RhB retention by the sorbent were calculated. The positive value of ΔH confirms the endothermic behavior of the adsorption of RhB by PPs from aqueous solution. The positive value of entropy (ΔS = 42.17 J mol–1 K–1) of the sorption of RhB onto the sorbent surface may be attributed to the increase in the degree of freedom of the RhB molecules is more restricted in the PPs structure than in solution.